Screening for autism spectrum disorder in low- and middle-income countries: A systematic review - Stewart, Lydia A; Lee, Li-Ching (Autism : the international journal of research and practice, 2017)
This review contributes to the growing body of global autism spectrum disorder literature by examining the use of screening instruments in low- and middle-income countries with respect to study design and methodology, instrument adaptation and performance, and collaboration with community stakeholders in research. A systematic review was conducted to understand the use of autism spectrum disorder screening instruments in low- and middle-income countries from studies published between 1992 and 2015. This review found that 18 different autism spectrum disorder screeners have been used in low- and middle-income settings with wide ranges of sensitivities and specificities. The significant variation in study design, screening methodology, and population characteristics limits the ability of this review to make robust recommendations about optimal screening tool selection. Clinical-based screening for autism spectrum disorder was the most widely reported method. However, community-based screening was shown to be an effective method for identifying autism spectrum disorder in communities with limited clinical resources. Only a few studies included in this review reported cultural adaptation of screening tools and collaboration with local stakeholders. Establishing guidelines for the reporting of cultural adaptation and community collaboration procedures as well as screening instrument psychometrics and screening methodology will enable the field to develop best practices for autism spectrum disorder screening in low-resource settings.